Implementing Systemic Innovation Strategies for a More Sustainable Future: The Case of Three Overseas Countries and Territories - Toffanin, Renato; Jezic von Gesseneck, Milan (Frontiers in Research Metrics and Analytics, 2022)
For sustainable development is often seen as a process within the context of globalization, covering the economic, social and environmental dimensions. In recent years, the rapid pace of globalization has accelerated change in all of these dimensions thus causing trends and processes in various spheres to interact with one another in unpredictable ways. Particularly complicated problems, such as the COVID-19 pandemic, make it more difficult to address individual issues without facing the risk of unintended consequences. This uncertainty poses a further challenge for decision-makers tasked with defining sustainable policies that effectively address intertwined problems. Indeed, this also raises the question of a more inclusive and holistic approach to innovation policies that takes up such a complex issue. Thus, addressing sustainability challenges implies a radical systemic change in multiple dimensions, including policy, culture and civil society. This also means that there are no blueprints for the governance of critical sustainability issues both at the local and global levels. As a result, policymakers should be adopting a learning process rather than imposing decisions. As to the COVID-19 and other complex issues, we argue that suitable policies should be developed and fine-tuned over time through a collective, social endeavour. Here, we propose a shared methodology based on ‘backcasting’, a specific type of foresight, to facilitate policy learning (and thus policy-making) within a wide range of territories, regardless of their wealth, geographic characteristics and internal political organisation. This methodology was developed in the context of the Territorial Strategies for Innovation (TSI) programme funded by the 10th European Development Fund from April 2014 to April 2020. The overall objective of our assignment was to build capacity and raise awareness within the EU’s Overseas Countries and Territories about policy-making and implementation of innovative approaches to development. Incorporating a systemic innovation perspective, this innovative approach highlights novel options and opportunities for defining adequate policies to positively impact sustainable development and long-term transformative change during these uncertain times. Here we present the illustrative cases of Anguilla, Curaçao and New Caledonia.